2002
DOI: 10.1136/thorax.57.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide correlates with airway eosinophils in childhood asthma

Abstract: Background: Exhaled nitric oxide has been proposed as a marker for airway inflammation in asthma. The aim of this study was to compare exhaled nitric oxide levels with inflammatory cells and mediators in bronchoalveolar lavage fluid from asthmatic and normal children. Methods: Children were recruited from elective surgical lists and a non-bronchoscopic bronchoalveolar lavage (BAL) was performed after induction of anaesthesia. Exhaled nitric oxide (parts per billion) was measured by two techniques: tidal breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
1
8

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(157 citation statements)
references
References 24 publications
6
142
1
8
Order By: Relevance
“…16,22 In subjects with mild asthma, F ENO correlates with the magnitude of airway eosinophilia 23 and bronchial hyper-responsiveness 24 and falls in a dose-dependent manner after the initiation of ICS. 25 Accordingly, F ENO in our study was lower in children with mild-to-moderate asthma treated with lower doses of ICS than in children with severe asthma on twice the amount of daily ICS.…”
Section: Discussionmentioning
confidence: 99%
“…16,22 In subjects with mild asthma, F ENO correlates with the magnitude of airway eosinophilia 23 and bronchial hyper-responsiveness 24 and falls in a dose-dependent manner after the initiation of ICS. 25 Accordingly, F ENO in our study was lower in children with mild-to-moderate asthma treated with lower doses of ICS than in children with severe asthma on twice the amount of daily ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of F eno as an indicator of pulmonary infl ammation is relatively simple and inexpensive compared with other biomarkers, so there is great interest in the potential role for using F eno data in asthma management. F eno level has been shown to correlate with lung function, sputum eosinophil levels, and methacholine responsiveness, [9][10][11][12][13][14][15][16][17] and, therefore, may provide a noninvasive change of Ն 10 ppb for those with lower categories of infl ammation. We applied this algorithm, modifi ed for pediatric cut points (if F eno level increased by Ն 7 ppb for those with F eno values , 35 ppb or Ն 20% for those with F eno Ն 35 ppb) and found that a "significant" change in F eno level from the previous visit did not predict future health-care use ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are less likely given prior studies that demonstrate reproducibility of F eno measurements 34,35 and the strong, existing evidence of correlation between eosinophilic airway infl ammation and F eno level. 9,11,[13][14][15][16][17] There were limitations to the study design that warrant consideration. As our study population was limited to children in Baltimore City, results may not be generalizable to other populations.…”
Section: Role Of Sponsorsmentioning
confidence: 99%
“…Le FE NO est corrélé à l'éosinophilie sanguine [76] , au pourcentage d'éosinophiles présents dans l'expectoration induite [65,66] , au nombre d'éosinophiles présents dans la muqueuse [77] et le LBA [78] . Bien qu'un taux de NO supérieur à 42 ppb reflète généralement une éosinophilie de l'expectoration supérieure ou égale à 3 % avec une bonne fiabilité, un traitement par hautes doses de corticostéroïdes inhalés et un statut tabagique ou atopique peuvent altérer les seuils de NO qui identifient le phénotype inflammatoire éosinophilique [66] .…”
Section: Intérêt Pour L'identification Des Phénotypes Inflammatoires unclassified